2019
DOI: 10.1515/ijeeps-2018-0292
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Component-Based Improved Passive Islanding Detection Method for Distribution System with Distributed Generations

Abstract: In distributed generation (DG) systems, the rate of change of voltage and the rate of change of frequency are the two most common and widely used simple and low-cost passive islanding detection schemes. Unfortunately, these passive islanding detection schemes find limitation for detecting the islandings that cause very small power imbalance. In this paper, an improved passive islanding detection scheme is proposed by using the two newly derived indices from the sequence components of the current signal with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Intentional islanding is a somehow planned situation whereas unintentional islanding occurs during several changes in the system [24]. The major challenge faced by the system due to the addition of ADGs is unintentional islanding, leading to various problems of insufficient grounding of equipment and two-way power flow, causing the loss of safety of workers, affecting the synchronism of the voltage and frequency of synchronous generators and converters (inverters) [25,26], and causing power quality (sag and swell) issues due to the reverse power flow phenomena. Islanding identification is a crucial and challenging job involved with integrated power distribution networks [27][28][29][30][31][32].…”
Section: Problem Statement and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Intentional islanding is a somehow planned situation whereas unintentional islanding occurs during several changes in the system [24]. The major challenge faced by the system due to the addition of ADGs is unintentional islanding, leading to various problems of insufficient grounding of equipment and two-way power flow, causing the loss of safety of workers, affecting the synchronism of the voltage and frequency of synchronous generators and converters (inverters) [25,26], and causing power quality (sag and swell) issues due to the reverse power flow phenomena. Islanding identification is a crucial and challenging job involved with integrated power distribution networks [27][28][29][30][31][32].…”
Section: Problem Statement and Literature Reviewmentioning
confidence: 99%
“…The kind of ADG and system parameters will have a big impact on the technique choice for islanding detection [57,63]. In recent years, hybrid IDSs have been proposed, and it appears that the hybrid IDSs are the best option for detecting islanding when changes in system parameters are significant and when launching an active IDS when those changes are not significant enough for a passive IDS to make an absolute unequal treatment [25,94].…”
mentioning
confidence: 99%
“…The sequence component-based improved passive islanding detection method has been proposed for DNs with distributed generation technologies [155]. The authors identified a shortcoming of passive islanding detection strategy in terms of their incapability of determining or detecting island the results in a slight power imbalance.…”
Section: Recent Trends In Dn With Dg and Future Directions 51 Recent Research On Grid-integrated Systemsmentioning
confidence: 99%
“…Also, it has high computational complexity. In [26], passive IDT based on zerosequence current and negative sequence current is used. Here, three types of threshold values are used to discriminate the islanding from the non-islanding events that increase the computational cost and also increases the detection time.…”
Section: Introductionmentioning
confidence: 99%